Multilingual Dictionary of the Headwords of the Academic Words List Russian, Belarusian, Bulgarian, Ukrainian and Polish - Шестакова, Катерина Юріївна (Verlag Dr. Kovač, 2022)
We would like to present the first multi-language dictionary compiled specifically for an Academic Word List (AWL). It follows the publication of the AWL by Averil Coxhead in 2000. The original AWL made in English has been translated by scholars from the field of human and social sciences into Russian, Belarusian, Bulgarian, Ukrainian and Polish. Originally the AWL was created for teachers to use as part of a teaching programme preparing students for tertiary level study or for students working alone to learn the words most needed to study at higher educational establishments (Coxhead, 2000).
Keywords: Academic Words List, Ukrainian, English